Dynamics of residual shunt closure within one year after endovascular patent foramen ovale closure: a clinical study - A. S. Tereshchenko; E. V. Merkulov (Кардиоваскулярная терапия и профилактика)
Aim. To study 12-month dynamics of residual shunt (RS) closure after endovascular patent foramen ovale (PFO) closure.Material and methods. We analyzed the data of 80 patients who underwent endovascular PFO closure at the Chazov National Medical Research Center for Cardiovascular Diseases in the period 2018-2023. All patients underwent a full range of examinations in accordance with current clinical guidelines. The severity of RS immediately after occluder implantation, as well as after 1, 6 and 12 months post-intervention assessment was based on transesophageal echocardiogram bubble study at the control visit.Results. In the postoperative period, RS was visualized in 17,5% (n=14) of patients. Discharge was significant in 7,5% (n=6) of patients. One month after the intervention, residual significant discharge persisted in 10,0% (n=8) of patients. After 6 months, RS was visualized in 2,5% (n=2) of patients, and after 12 months, only in one patient (1,3%). The proportion of patients with RS 1 month after the intervention decreased to 42,9%, after 6 months to 85,7%, and after 12 months to 92,9% (p<0,05).Conclusion. Most patients with RS after endovascular intervention for PFO are characterized by complete endocardialization of the occluder and PFO closure within the first year.